Sosialisasi Hidup Berdampingan Dengan Covid 19 dan Pemeriksaan Kesehatan (Asam Urat, Kgd dan Tekanan Darah) Pada Lansia di Desa Dolok Nauli / Lobupining Kecamatan Adiankoting Kabupaten Tapanuli Utara Tahun 2022 - Naomi Isabella Hutabarat; Janner Pelanjani Simamora; Elly Sianturi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The world is currently undergoing changes in all fields including lifestyle and mindset. This change is further caused by the spread of covid in the last two years, which makes all parties have to make the best decisions. One of the goals is to provide knowledge to the elderly about the importance of socialization of coexistence with covid 19. Counseling on the socialization of coexistence with covid 19 in the elderly and health checks (Uric Acid, KGD and Blood Pressure) in Dolok Nauli Village / Lobupining Adiankoting District 20 people. Counseling and discussion about the socialization of coexistence with covid 19 in the elderly went well and smoothly and the elderly group was enthusiastic and excited in responding to the counseling that was carried out.